Human Parainfluenza Virus Type 1 Matrix and Nucleoprotein Genes Transiently Expressed in Mammalian Cells Induce the Release of Virus-Like Particles Containing Nucleocapsid-Like Structures - Coronel, Elizabeth C. (American Society for Microbiology, 1999)
The matrix (M) protein plays an essential role in the assembly and budding of some enveloped RNA viruses. We expressed the human parainfluenza virus type 1 (hPIV-1) M and/or NP genes into 293T cells using the mammalian expression vector pCAGGS. Biochemical and electron microscopic analyses of transfected cells showed that the M protein alone can induce the budding of virus-like particles (vesicles) from the plasma membrane and that the NP protein can assemble into intracellular nucleocapsid-like (NC-like) structures. Furthermore, the coexpression of both the M and NP genes resulted in the production of vesicles enclosing NC-like structures, suggesting that the hPIV-1 M protein has the intrinsic ability to induce membrane vesiculation and to incorporate NC-like structures into these budding vesicles.